2005
DOI: 10.1152/ajpheart.00265.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial microparticles affect angiogenesis in vitro: role of oxidative stress

Abstract: Endothelium-derived microparticles have recently been described as a new marker of endothelial cell dysfunction. Increased levels of circulating microparticles have been documented in inflammatory disorders, diabetes mellitus, and many cardiovascular diseases. Perturbations of angiogenesis play an important role in the pathogenesis of these disorders. We demonstrated previously that isolated endothelial microparticles (EMPs) impair endothelial function in vitro, diminishing acetylcholine-induced vasorelaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 41 publications
10
140
1
2
Order By: Relevance
“…Taraboletti et al demonstrated that although the low concentrations of MVs isolated from HUVECs promote angiogenesis in vitro, the high concentrations of endothelial-derived MVs suppress angiogenesis [83] . In accordance with these results, Mezentsev and colleagues reported that isolated endothelial-derived MVs in pathophysiological concentrations impair angiogenesis in vitro by affecting all parameters of capillary-like network formation [84] . In addition, the MVs isolated from T2DM patients with CAD fail to induce angiogenesis, which may partially explain the lack of vascular regeneration characterization in T2DM with CAD [35] .…”
Section: Mvs and Angiogenic Effectssupporting
confidence: 53%
“…Taraboletti et al demonstrated that although the low concentrations of MVs isolated from HUVECs promote angiogenesis in vitro, the high concentrations of endothelial-derived MVs suppress angiogenesis [83] . In accordance with these results, Mezentsev and colleagues reported that isolated endothelial-derived MVs in pathophysiological concentrations impair angiogenesis in vitro by affecting all parameters of capillary-like network formation [84] . In addition, the MVs isolated from T2DM patients with CAD fail to induce angiogenesis, which may partially explain the lack of vascular regeneration characterization in T2DM with CAD [35] .…”
Section: Mvs and Angiogenic Effectssupporting
confidence: 53%
“…Indeed, low concentrations of EMPs have been observed to have proangiogenic properties by regulation activity of matrix metalloproteinases produced by endothelial cells. 11 In contrast, high concentrations of EMPs decreased the formation of capillary-like structures by stimulation of the production of reactive oxygen species and thus showing antiangiogenic properties. 12 Jimenez et al have suggested that analysis of EMP phenotypic profile may provide clinically useful information on the status of the endothelium.…”
Section: Endothelial Microparticles As a Mirror Of Endothelial Functionmentioning
confidence: 98%
“…60 Further details on the molecular mechanisms of MP effects on vascular reactivity can be found in Martinez et al 64 Finally, endothelial, platelet, and tumor cell-derived MPs seem to be able to stimulate angiogenesis, an effect mediated by reactive oxygen species, metalloproteinases, growth factors such as vascular endothelial growth factor, or sphingomyelin. [65][66][67][68][69] Apoptotic bodies from endothelial cells (larger than MPs) could also contribute to tissue repair mechanisms by stimulating the differentiation of progenitor cells. 70 …”
Section: Plasma Levels Of Mps In Cardiovascular Diseasesmentioning
confidence: 99%